An investigation into adolescents' experience of cognitive behavioural therapy within a child and adolescent mental health service. (April 2013) - Donnellan, Deanna; Murray, Craig; Harrison, James
Cognitive Behavioural Therapy (CBT) is frequently referenced within NICE (National Institute for Clinical Excellence) guidance and is a recommended psychological therapy for a number of different mental health disorders for both adults and children. This is due to the current body of quantitative research around CBT demonstrating its efficacy for a range of mental health difficulties. However, CBT has not been as well addressed within the qualitative field and this gap in research is even more obvious when looking at CBT conducted with children and adolescents. This interpretative phenomenological study explored adolescents' experiences of a course of CBT within a Child and Adolescent Mental Health Service (CAMHS) in a one-to-one format. Three female adolescents who had completed an agreed contract of therapy with the CBT service took part in semi-structured interviews. Four superordinate themes emerged from analysis and highlighted components within CBT that were important to the sample. These were engagement, the therapeutic relationship, the impact of CBT on change and the manner in which CBT was delivered. The findings are discussed with relevance to current policy and pertinent literature as well as implications for service delivery and future research.